Forecasting the Number of Sales of Mie Sedap at PT. Wings Surya Probolinggo Branch With Single Exponential Smoothing Method - Ismiwati Chalifah (Yayasan Insan Mulia Bima, 2024)
PT. Wings Surya branch Probolinggo is a business engaged in trading, especially distributors of foodstuff sales, one of which is instant noodles with the brand “Mie Sedap.” As the competition level becomes more competitive, the company must be able to know the estimated sales forecast for the future. PT has not done this. Wings Surya Branch Probolinggo. So this study aims to assist the company in understanding its sales forecasting in the future. This research uses a single exponential smoothing method because it is based on the analysis of sales data in the company and the data pattern formed according to the criteria of the way to be used. The process of calculating this method is to find a single smoothing value; then, it will get the forecasting value. After going through various stages calculation process done with the amount of sales data from January 2013 to December 2015, the result of this research is forecasting sales of Mie Sedap Goreng 90 gr products in January 2016 as much as 156873 boxes. It is based on the smallest MAPE value, which is 2,22 at alpha 0,9, and the accuracy of the average forecasting with testing data from January to June 2016 then obtained the result of 92,29%. So the effects of sales forecasting received can help companies know the estimated sales and can be used in supporting decision-making appropriately.